2015
DOI: 10.1212/cpj.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Clinical perspectives on medical marijuana (cannabis) for neurologic disorders

Abstract: SummaryThe American Academy of Neurology published an evidence-based systematic review of randomized controlled trials using marijuana (Cannabis sativa) or cannabinoids in neurologic disorders. Several cannabinoids showed effectiveness or probable effectiveness for spasticity, central pain, and painful spasms in multiple sclerosis. The review justifies insurance coverage for dronabinol and nabilone for these indications. Many insurance companies already cover these medications for other indications. It is unli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
0
15
0
2
Order By: Relevance
“…In animal studies, marijuana and derivatives have been reported to provide protection, in some form, of the substantia nigra and as such reduce those neurons from damage or deterioration [9]. What should also be noted, similar findings have also been observed for Huntington's disease, MS, and Alzheimer's disease [1]. One of the major issues with using the herbal form of this drug for treatment relates to inconsistent concentrations of the active ingredients from available sources [10].…”
Section: Editorialmentioning
confidence: 74%
See 2 more Smart Citations
“…In animal studies, marijuana and derivatives have been reported to provide protection, in some form, of the substantia nigra and as such reduce those neurons from damage or deterioration [9]. What should also be noted, similar findings have also been observed for Huntington's disease, MS, and Alzheimer's disease [1]. One of the major issues with using the herbal form of this drug for treatment relates to inconsistent concentrations of the active ingredients from available sources [10].…”
Section: Editorialmentioning
confidence: 74%
“…Medical (herbal) marijuana (Cannabis sativa) is becoming a popular therapy for treatment of degenerative neurological diseases, including Parkinson's disease (PD) and other medical conditions [1,2]. Extracts from this plant have been used by ancient herbal practitioners over millennia in the treatment for a wide variety of diseases, which forms the basis of many claims today [3].…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…La evidencia señala que el UMC puede conllevar efectos beneficios para abordar ciertas condiciones de salud (Bourne, 2015;Khaiser et al, 2017;Lahat, 2017;Spencer, Shaw, & Slaven, 2017;Stinson & DeAngelis, 2017;Tellioğlu & Tellioğlu, 2017). Si bien existe necesidad de mayor información y ensayos controlados aleatorios (Ciccone, 2017;Hill, 2014;Koliani-Pace & Siegel, 2016;Kondrad & Reid, 2013;Pinkas, Jabłoński, Kidawa, & Wierzba, 2016), ciertos estudios preliminares han sugerido que el UMC puede ser beneficioso en el tratamiento de ciertas condiciones como inflamaciones, espasticidad, epilepsia, trastornos de la alimentación, glaucoma, enfermedades inflamatorias intestinales, y trastornos neurológicos (Ahmed & Katz, 2016;Alexander, 2016;Fife, Moawad, Moschonas, Shepard, & Hammond, 2015;Maida, 2017;Lahat, 2017;Patel, 2016;Peters, 2013).…”
Section: Beneficios Del Umcunclassified
“…Die CB1-Rezeptoren sind vorwiegend im zentralen Nervensystem (u. a. Basalganglien, limbisches System, Rückenmark), aber auch in der Herz-und glatten Muskulatur, sowie in Endothelzellen lokalisiert. CB2-Rezeptoren finden sich auf immunregulatorischen und hämatopoetischen Zellen, aber auch im zentralen Nervensystem, u. a. ebenfalls in den Basalganglien, wieder [8,9].…”
Section: üBerblick üBer Verschreibungsfähige Cannabisprodukteunclassified